Evaluating Passenger Load Factor of Public Bus Services in West Klang Valley - Norhisham S.; Abu Bakar M.F.; Abd Samad Z.H.; Syamsir A.; Zaini N.; Katman H.Y.; Ramli M.Z. (Springer, 2023)
Buses; Landforms; Quality of service; Telecommunication services; Transportation; Urban transportation; Bus services; Passenger loads; Public transportation; Public transportation services; Services quality; Urban areas; Valley network; Waiting-time; Bus transportation